TINDAK TUTUR ILOKUSI DALAM LIRIK LAGU TAFSIR MISTIK KARYA THE PANTURAS: KAJIAN PRAGMATIK J.L. AUSTIN - Bea Anantha Damanik; Meyla Zinta Syahputra; Suaidah Siregar; Ayu Nadira Wulandari (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to analyze illocutionary speech acts in the lyrics of Tafsir Mistik based on J.L. Austin’s theory, which categorizes illocutionary acts into five types: verdictive, exercitive, commissive, behabitive, and expositive. As a form of artistic communication, song lyrics play a crucial role in conveying messages to listeners. With Tafsir Mistik by The Panturas as the object of study, the communicative messages in song lyrics can include emotions, ideas, social criticism, or perspectives on life, expressed through words and symbols. Tafsir Mistik serves as an example of a song that critiques the phenomenon of superficial thinking in the social media era. The analysis results indicate that the song’s lyrics contain various illocutionary speech acts that reinforce its social message. The study concludes that the lyrics of Tafsir Mistik not only function as an artistic expression but also as an effective communication tool for delivering social messages.